Development of a Computerized Student- Advising and Enrollment System - Greg Sambaan Campos (Alliance of Health Activists (AloHA), 2019)
The traditional “paper and pen” method of student records handling manual enrolment system has been bungling the advising and enrolment process every semester. More related issues were raised by stakeholders who compelled the school to acquire and install a new system. The fundamental objective of the system was to bring the level of student record into a structured form. With such a mindset, the system was assumed to consequently improve the conduct of advising and enrolment processes in the school. To expedite the comparison, the author chose the queuing methodology as it allows generate low – cost and affordable technologies include SMS as well as barcode which area also injected into the computerized enrolment system. Further, in programming the application system, the author as FOSS advocate himself, used open – source web engineering tools along the lines of Apache 2 for web service, PHP 5 for server – side scripting, MYSQL for database service, XML AJAX, Code 3 of 9 bar coding technique as well as POSIX – based regular expressions. The development and full – scale implementation of this system had physically changed the landscape of student records handling in the school as student checklists and allied reports can be easily retrieved by deputized users from designated workstations. The enrolment process had significantly improved specifically in terms of advisee and adviser interaction. This becomes possible as advisers have already the luxury of time to talk and exchange ideas with their advisees. While under operational observation, the system will be of exclusive use of the school until proven to be already stable. The rest of the departments will likewise avail of the service in the near future as the application system is designed to be scalable for such expansion. Keywords: automated system; enrolment system; SMS; student records; system development